(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The paper investigates the interior and furniture of one of the biggest public buildings in Sofia, built in the period 1978–1981 – the National Palace of Culture (NPC). The study is focused on the evaluation of interior design, items and zones, in relation to the design solutions of key public interiors, which were widespread during the socialist period; and follows their presentation in professional publications of the period. The aim of the paper is to reveal the visual messages concentrated in the building and its interior spaces. Thus, researching the National Palace of Culture from the point of view of architecture and interior design specific features are revealed of the development of the contemporary history of design and the arts helps to define the understanding of artistic values, as well as the evolution and preservation of the cultural heritage of the 20th century.